Microplastics in River Water: Raising Science Competencies and Enviromental Awarness in Secondary Education - Adean Mayasri; Muhammad Reza; Hayatul Aula (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2025)
Guided by the PISA 2025 science framework, this study aimed to develop and validate microplastics-based chemistry teaching materials using the Four Steps Teaching Material Development (4S-TMD) model and to evaluate their impact on students’ science competencies and environmental profiles. The research employed a research-and-development (R&D) design based on the 4S-TMD stages of selection, structuring, characterization, and didactic reduction. The participants were 30 upper-secondary students (15 Grade 10 and 15 Grade 11) from Teuku Nyak Arif Fatih Bilingual School. Additional data were obtained from expert validators who reviewed the teaching materials and assessment instruments, and from microplastics identified in water samples from the Krueng Daroy River as the empirical context. The instruments comprised microplastics-based teaching materials and evaluation sheets measuring students’ science competencies and environmental profiles. Expert validation showed that the content validity ratio of the teaching materials and assessment sheets increased to acceptable values (CVR up to 1.00), indicating that all items were essential and aligned with the PISA 2025 framework. Independent-samples t-tests indicated significantly higher science competency and environmental profile scores for Grade 11 than for Grade 10 students (p < 0.05). Overall, the microplastics teaching materials developed using the 4S-TMD model were valid and showed potential effectiveness in supporting students’ ecological awareness and science competencies in line with the PISA 2025 framework.